Analisa Pengaruh Kepuasan Kerja, Keterlibatan Kerja Dan Iklim Organisasi Terhadap Kinerja Pegawai Dinas Pendidikan Kabupaten Nganjuk - Dwi Andari, Sri Anida Kusumawati (Otonomi, 2021)
The purpose of this study is to analyze the effect of job satisfaction, job involvement and organizational climate on employee performance at the Nganjuk District Education Office simultaneously and to analyze the effect of job satisfaction, job involvement and organizational climate on employee performance in the Nganjuk Regency Education Office partially. The population used in this study were all 100 employees of the Nganjuk Regency Education Office. While the sample to be used in this study is the entire population, namely the staff of the Nganjuk Regency Education Office by using the census model, so that the population members of 100 people are all samples in this study. The analytical method used in this research is multiple linear analysis model. The results showed that Job Satisfaction, Job Involvement and Organizational Climate had an effect on Employee Performance at the Nganjuk Regency Education Office simultaneously. There is no influence between Job Satisfaction (X1) on Employee Performance (Y) partially in the Nganjuk Regency Education Office. There is a partial influence of the involvement variable on Employee Performance (Y) and there is an influence between Organizational Climate (X3) on Employee Performance (Y).